2021
DOI: 10.1002/srin.202100035
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Corner Cracks in Hypoperitectic Microalloyed Steel Billets

Abstract: Due to the development of continuous casting technology, the incidence of cracks in the continuous casting process has been significantly reduced. However, a few small cracks still appear during the continuous casting of special steel. For instance, cracks often appear at the corner of the billet during the production of hypoperitectic microalloyed steel. Most research on the causes of corner cracks in hypoperitectic microalloyed steel has focused on investigating the hot ductility of steel and not considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Therefore, there are different understandings of the location for the formation of corner transverse cracks in microalloyed steel slabs. Many previous studies [2][3][4][5][6][7] considered that transverse corner cracks were mainly affected by improper oscillation and mold flux as well as evident fluctuation of mold level. When the friction force and thermal stress are larger than the threshold of steel, transverse corner cracks would occur at the troughs of oscillation marks.…”
Section: Initiation Of Transverse Corner Cracksmentioning
confidence: 99%
“…Therefore, there are different understandings of the location for the formation of corner transverse cracks in microalloyed steel slabs. Many previous studies [2][3][4][5][6][7] considered that transverse corner cracks were mainly affected by improper oscillation and mold flux as well as evident fluctuation of mold level. When the friction force and thermal stress are larger than the threshold of steel, transverse corner cracks would occur at the troughs of oscillation marks.…”
Section: Initiation Of Transverse Corner Cracksmentioning
confidence: 99%
“…Before rolling, the microcrack is in an upright V-shape. [11,21] As the slab moves to the left, the side-1 of the microcrack is the first to come into contact with the roll and deforms in the RD direction. Subsequently, the side-2 of the microcrack also comes into contact with the roll and deforms in the RD direction.…”
Section: Deformation Behavior Of Surface Microstructure On the Contin...mentioning
confidence: 99%
“…These cracks are large in size and simple in morphology and can be seen directly and clearly without treatment of the plate surface. [7][8][9][10][11][12] Sarkar et al studied the causes of corner defects and longitudinal cracks in the hotrolled plate of C-Mn steel. [7] The article concluded that the surface cracks in the hot-rolled plate were due to surface defects in the continuous casting slab by observing the morphology of the crack and the inclusions inside the cracks.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Hanao et al studied cracks caused by uneven solidification in the mold [22] and Xing et al studied cracks caused by additional mechanical stress due to mold wear. [23,24] Therefore, crack formation is a highly complex phenomenon worth investigating.…”
Section: Introductionmentioning
confidence: 99%